Social Demographics and Physical Distancing Knowledge of Sports Teachers and Students Against the Prevention of the Coronavirus (Covid-19) Pandemic - Syamsulrizal Syamsulrizal; Yeni Marlina; Muhammad Iqbal (STAI Hubbulwathan Duri, 2022)
The Corona pandemic requires good knowledge from sports teachers and students. This study aims to determine how the socio-demographic characteristics of sports teachers and students in Lhokseumawe City, knowledge of physical distancing and socio-demographic relations to the knowledge of physical distancing of teachers and students of sports in Lhokseumawe City. The subjects of this study were teachers and students of sports in Lhokseumawe City. The sample size is 304 respondents. This study applied a questionnaire as primary data. Respondents who participated in this research amounted to 304 respondents. The results showed that all data were valid with a calculated r value r table and reliable with a Cronbach alpha value 0.6. The average respondent's knowledge of physical distancing is 4.27, which means that knowledge about Physical Distancing for the prevention of the Corona Virus ( Covid-19 ) pandemic for sports teachers and students in Lhokseumawe City was very good. Respondents' social-demographic indicators (gender, age, last education, marital status, occupation, activity (involvement) in sports activities and income had a significant relationship on 9 indicators of knowledge about physical distancing to prevent the Corona Virus ( Covid-19 ) pandemic. On teachers and sports students in Lhokseumawe City, the rest there is no significant relationship. Respondents' social-demographic indicators to indicators of knowledge about physical distancing, namely